Right to a (Healthy) Environment How to Come Closer to the Implementation? Good Examples from the Practice of the Hungarian Constitutional Court - Bándi Gyula; Tahyné Kovács Ágnes (STUDIA IURIDICA LUBLINENSIA, 2024)
The paper discusses how the right to a healthy environment and the supportive principles could enter into the practice of the Constitutional Court in Hungary over the past 30 years. Beginning with a short survey of the legislative development is presented, following with the discussion of the constitutional interpretation, which commenced with the principle of non-regression, together with the necessity-proportionality test, and the need to give flesh to the bones of constitutional rights – explicitly, institutionalize them – could come parallel with these principles. Later the precautionary approach and the interests of future generations – even a public trust doctrine – could be incorporated in the Court practice. Needless to say, that while the theoretical and constitutional grounds are vital, what really matters are the institutional consequences and practical implementation. Still, if the scene is clear, the subsequent steps might be easier.